Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation (GI) Dengan Teknik Open-Ended Problem Terhadap Aktivitas dan Hasil Belajar Siswa SMAN 3 MATARAM - Rahmatullah Rahmatullah; Hairunnisyah Sahidu; Syahrial Ayub (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This is a quasi experiment research with nonequivalent control group design. This research aimed to examine the effect of cooperative learning model type GI with open-ended problem technique toward activity and physics learning outcome of students. The population of this research is all students of class XI IPA SMAN 3 Mataram in academic year 2016/2017. The Sampling technique used is purposive sampling to get the students of class XI IPA 6 as experiment group and XI IPA 5 as control group. The experiment group was treated with cooperative learning model type GI with open-ended problem technique while control group was treated with cooperative learning model type GI. The instruments used for learning activities are non-test instruments in the form of observation sheets and to measure the physics learning outcome used test instruments with multiple choice form. The research hypothesis was tested using manova test and t-test pooled variance. The results showed that there was an effect of cooperative learning model type GI with open-ended problem technique towards activity and physics learning outcome of the students.